Chuva de sementes e banco de sementes do solo como indicadores ecológicos de restauração para o bioma Pampa - Procknow, Djoney (2019)
The general aim of this study was to evaluate seed rain and soil seed bank as ecological indicators in different restoration strategies in Permanent Preservation Areas in Pampa Biome. The study was carried out in Caçapava do Sul, RS, in four different sites: 1) area under active restoration with applied nucleation, 2) passive restoration, 3) eucalyptus commercial plantation, and 4) reference site (seasonal forest). To analyze the seed rain, ten permanent collectors of 1 m² and 1 m in height were randomly implanted in each area. We collected seed rain monthly for twelve months. The evaluation of the number of seeds was performed by Kruskall-Wallis test (p <0.05). We evaluated diversity of seed rain by the morphospecies number, number of individuals, Margalef morphospecies richness, Pielou equitability and Shannon diversity. We analyzed floristic similiarity by Jaccard's similarity. We analyzed species composition and dispersion syndrome of each studied site through segmented correspondence analysis (DCA). We collected soil seed bank once, with a template of 0.25 cm x 0.25 cm at a depth of 5 cm from the soil surface. We collected ten random samples in each site. The samples were placed in plastic trays, randomly allocated on benches for germination in a shade house. We assessed soil seed bank quarterly for a period of twelve months. The number of germinated seeds and the dispersion syndrome were evaluated by Kruskall-Wallis test (p <0.05). We also calculated diversity index of Shannon, Pielou equitability and floristic similarity by the Jaccard index. The total number of seeds sampled in the seed rain was 239,888 and in the soil seed bank 1937 seeds germinated. The highest amount of seeds observed in seed rain was in the passive restoration site (190,249), Baccharis dracunculifolia DC. was the most representative species (98.41% of the seeds sampled). In the seed bank, the families with the greatest richness were Poaceae and Cyperaceae. The soil seed bank showed herbaceous predominance. In the seed rain, the area of passive restoration correlated to a greater degree with the anemocoric dispersion syndrome. In the seed rain, floristic similarity by the Jaccard index was higher between the active restoration areas and the native forest, the soil seed bank, presented a greater similarity between the active restoration area and passive restoration. The indicators evaluated were efficient to express the conditions of the regeneration mechanisms in the study region.